1992
DOI: 10.1200/jco.1992.10.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Activity of fludarabine in previously treated non-Hodgkin's low-grade lymphoma: results of an Eastern Cooperative Oncology Group study.

Abstract: Fludarabine is active in patients with previously treated NHL (particularly low-grade histologies). Future studies will examine its activity in combination with other chemotherapeutic agents in previously untreated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(48 citation statements)
references
References 10 publications
1
46
1
Order By: Relevance
“…[28][29][30] Fludara has been shown to be therapeutically efficacious against lymphoid malignancies. [31][32][33][34][35][36][37] In addition, it is an effective immunosuppressive drug 38,39 especially in conjunction with anti-T lymphocyte globulin (ATG), 39,40 and may possibly play a role in reducing the incidence and severity of graft-versus-host disease (GVHD). 41 We have recently demonstrated that it may be possible to achieve durable engraftment of donor hematopoietic stem cells while minimizing procedure-related toxicity using a low intensity conditioning regimen consisting of Fludara, busulfan (BU) and ATG prior to transplantation of granulocyte colony-stimulating factor (G-CSF)-mobilized allogeneic peripheral blood stem cells (alloSCT).…”
mentioning
confidence: 99%
“…[28][29][30] Fludara has been shown to be therapeutically efficacious against lymphoid malignancies. [31][32][33][34][35][36][37] In addition, it is an effective immunosuppressive drug 38,39 especially in conjunction with anti-T lymphocyte globulin (ATG), 39,40 and may possibly play a role in reducing the incidence and severity of graft-versus-host disease (GVHD). 41 We have recently demonstrated that it may be possible to achieve durable engraftment of donor hematopoietic stem cells while minimizing procedure-related toxicity using a low intensity conditioning regimen consisting of Fludara, busulfan (BU) and ATG prior to transplantation of granulocyte colony-stimulating factor (G-CSF)-mobilized allogeneic peripheral blood stem cells (alloSCT).…”
mentioning
confidence: 99%
“…The primary toxicity of fludarabine is myelosuppression, which may be prolonged in some patients, especially in those receiving higher doses or prolonged therapy [19][20][21]. Given the greater potential for serious myelotoxicity associated with greater fludarabine exposure, a shorter 3-day course may be a safer alternative when given in combination with mitoxantrone.…”
Section: Discussionmentioning
confidence: 99%
“…Phase I and phase II trials of fludarabine in patients with relapsed and refractory follicular lymphomas demonstrated response rates of 30%-60% [19][20][21]. When combined in vitro, fludarabine and mitoxantrone exert synergistic effects [22].…”
Section: Fludarabinementioning
confidence: 99%
“…Identification of new therapeutic agents for patients with relapsed diffuse large cell lymphoma is therefore needed. To date there is limited experience with nucleoside analogs such as fludarabine and cladribine in patients with relapsed or refractory DLBCL where responses have been disappointing (response rates 0-10%) [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%